The Role of Skeletal Stem Cells in the Reconstruction of Bone Defects. Issue 5 (July 2017) - Murphy, Matthew P.; Irizarry, Dre; Lopez, Michael; Moore, Alessandra L.; Ransom, Ryan C.; Longaker, Michael T.; Wan, Derek C.; Chan, Charles K.F.
Abstract : Abstract: Craniofacial surgery, since its inauguration, has been the culmination of collaborative efforts to solve complex congenital, dysplastic, oncological, and traumatic cranial bone defects. Now, 50 years on from the first craniofacial meeting, the collaborative efforts between surgeons, scientists, and bioengineers are further advancing craniofacial surgery with new discoveries in tissue regeneration. Recent advances in regenerative medicine and stem cell biology have transformed the authors' understanding of bone healing, the role of stem cells governing bone healing, and the effects of the niche environment and extracellular matrix on stem cell fate. This review aims at summarizing the advances within each of these fields.